Long-term dynamics of metazoan parasites in an age- and size-structured host population - Henriksen, Eirik Haugstvedt (UiT The Arctic University of Norway, 2021)
Parasites negatively affect hosts and may constitute serious management problems. At the same time, parasites are integral components of ecosystems and represent a substantial part of the biodiversity on earth. Understanding the ecological factors that influence the abundance and distribution of parasite populations is therefore important from a management perspective, but also to understand the mechanisms that shape populations and food webs. Parasites occur in complex food webs, with several opportunities for indirect effects. Ecosystem perturbations have been key to identify ecological processes that influence population and community dynamics. As some of these processes take a long time to unfold, they are only detectable from long-term studies. Unfortunately, few long-term studies have investigated host-parasite dynamics. The main aim of this thesis was to study how temporal changes in density and age- and size-structure of Arctic charr ( Salvelinus alpinus ) as a host species affected metazoan parasite dynamics across more than three decades of field observations from a subarctic lake. I also investigated the effects of the density of a competitor and predator, brown trout ( Salmo trutta ), on parasite abundance in the focal host Arctic charr. I documented that experimentally reducing the density of Arctic charr through culling reduced the prevalence and intensity of two trophically transmitted Dibothriocephalus tapeworm species. The decline in the parasite infections was mainly due to culling-induced changes in host population age structure and increased predation rates from brown trout. Furthermore, I found that changes in host body size explained most of the variation in the dynamics of Salmincola edwardsii gill lice, a directly transmitted copepod parasite. In this case, the density of brown trout surprisingly amplified transmission rates to Arctic charr. Finally, the abundance and aggregation of the long-lived swimbladder nematode Cystidicola farionis was chiefly driven by host-population age ...